2017
DOI: 10.1515/amcs-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

A robust algorithm to solve the signal setting problem considering different traffic assignment approaches

Abstract: In this paper we extend a stochastic discrete optimization algorithm so as to tackle the signal setting problem. Signalized junctions represent critical points of an urban transportation network, and the efficiency of their traffic signal setting influences the overall network performance. Since road congestion usually takes place at or close to junction areas, an improvement in signal settings contributes to improving travel times, drivers' comfort, fuel consumption efficiency, pollution and safety. In a traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Among these, 322 links represent the Grande Raccordo Anulare (GRA), which is a ring-shaped, 68.2 km long freeway that encircles Rome [30]. Further developments will deal with the analysis of the evolution over time through the use of a quasi-dynamic simulation [31], whose input are the same used in a static assignment, and with the study along urban arteries affected by traffic signals [32]. The simulations run on an Intel Xeon E5-2640 v3(2.60 GHz) processor and all the three scenarios converged (user equilibrium), on average, in 3-5 min.…”
Section: Traflc Simulation From Fcdmentioning
confidence: 99%
“…Among these, 322 links represent the Grande Raccordo Anulare (GRA), which is a ring-shaped, 68.2 km long freeway that encircles Rome [30]. Further developments will deal with the analysis of the evolution over time through the use of a quasi-dynamic simulation [31], whose input are the same used in a static assignment, and with the study along urban arteries affected by traffic signals [32]. The simulations run on an Intel Xeon E5-2640 v3(2.60 GHz) processor and all the three scenarios converged (user equilibrium), on average, in 3-5 min.…”
Section: Traflc Simulation From Fcdmentioning
confidence: 99%
“…In addition, also being the simulation computationally expensive, the extensive exploration of the entire solution domain would imply unacceptable calculation time [33]. To avoid these problems, the Surrogate Method is introduced, first for manufacturing problem and then also for transportation problem [1,9,34]. is method combines the advantages of stochastic approximation type of algorithm with the ability to obtain sensitivity estimates.…”
Section: Contribution Of the Papermentioning
confidence: 99%
“…In previous studies, it is demonstrated the capacity of the Surrogate Method (SM) to find central optimal solution to problems concerning signal setting and combined signal setting, due to its ability to jump out of local minimum. Hence, it is showed the efficacy and the efficiency of the SM with respect to the Projected Gradient Algorithm (PGA), the Particle Swarm Optimization (PSO), and the Genetic Algorithm (GA) (see [9,35]). Given the complexity of this problem, a spatial decomposition method is introduced.…”
Section: Contribution Of the Papermentioning
confidence: 99%
See 2 more Smart Citations